Analisis laporan keuangan untuk menilai kinerja keuangan Pemerintah Daerah Kabupaten Minahasa Selatan Tahun 2021-2023 - Wawolangi, Syalomita Gabrilia Vanesa; Morasa, Jenny; Tirayoh, Victorina Z. (Riset Akuntansi dan Portofolio Investasi, 2025)
Measuring the financial performance of local governments is very important because it provides a clear picture of the efficiency, effectiveness, and accountability of the use of public resources. By measuring financial performance, local governments can ensure that the budget used is in accordance with the goals and development priorities that have been set, and detect potential deviations or waste. This study aims to assess the Financial Performance of the South Minahasa Regency Government in 2021-2023 in terms of the Financial Ratio. The object of this research is the Minahasa Selatan Regency Government. This study uses a qualitative research method. The analysis techniques used are the Regional Original Revenue Effectiveness Ratio, Regional Financial Efficiency Ratio, Expenditure Harmony Ratio, Revenue and Expenditure Growth Ratio, and Regional Financial Independence Ratio. The results of the study show that the financial performance of the Minahasa Selatan Regency Government in terms of the Regional Original Revenue Effectiveness Ratio is classified as less effective because the average ratio only reaches 87.89%. The Regional Financial Efficiency Ratio is classified as efficient with an average result obtained of 99.41%. The Financial Harmony Ratio of South Minahasa Regency is categorized as harmonious with the allocation of part of the funds for operational expenditures averaging 67.02% and capital expenditures an average ratio of 8.82%. The Regional Original Income Growth Ratio has decreased, the Regional Income Growth Ratio has experienced positive growth, the Regional Expenditure Growth Ratio shows a stable increasing trend. The Regional Financial Independence Ratio is classified as very low with an average ratio of only 3.40% with an instructive relationship pattern.